131 Producer adoption of preconditioning strategies in the Oklahoma Quality Beef Network. (28th November 2020) - Robe, Jeff; Beck, Paul A; Zook, Dana; New, Marty; Ward, Earl; Freking, Brian
Abstract: The Oklahoma Quality Beef Network (OQBN) Vac-45 program was designed to provide health management certification and value-added marketing for cow-calf producers since 2001. The objective of this abstract is to examine trends in health management systems by OQBN participants. Participants chose from one of three options for administering vaccinations: Option 1) branding and weaning, Option 2) 2–6 weeks before weaning and weaning, Option 3) weaning and 14–28 d post weaning. From 2014–2018, 596 participants enrolled 30, 452 calves. Preferred vaccine options were: Option 1) 210 participants (35%) and 12, 015 calves (37%), Option 2) 96 participants (16%) and 3, 016 calves (10%), Option 3) 290 participants (49%) and 15, 421 calves (51%). Producer choice of a viral vaccine component included 251 (42%) participants using killed vaccine at least once. A five-yr average of cattle marketed with at least one modified-live vaccine (MLV) exposure was 73% of calves (22, 138) and 27% (8, 314) were treated with only killed vaccines. In Option 1, 57 (10% of the total) participants used killed vaccines at both times, 33 (6%) used a killed vaccine followed by a MLV at weaning, 120 (20%) used MLV at both times. Option 2, 55 (9%) participants used killed vaccines at both times, 4 (1%) participants used a killed vaccine follow by a MLV at weaning; 37 (6%) used a MLV at both times. Option 3, 114 (19%) participants used killed vaccines at both times, 2 (< 1%) participant used a killed vaccine followed by a MLV, 1 participant used MLV followed by killed vaccine, 173 (29%) participants used MLV at both times. Cattle marketed with killed vaccines have seen an increase in use; 2014 (27%), 2015 (17%), 2016 (27%), 2017 (31%), 2018 (39%). These data show the preferred method of MLV vaccination utilized is a weaning and post-weaning system with an increased use of killed vaccines, which may be due to producer concerns regarding exposure of brood cows to MLV.